Profiling and Characterization of Plant-Based Products Consumers in Chile - Campos-Jaque, Z (ASOC CASTELLANO-MANCHEGA DE SOCIOLOGIA, 2024)
The consumption trend of plant-based products has increased worldwide due to different reasons, and Chile has been a good example of this trend. Although sustainability, health, nutrition and taste may all seem to be main drivers for flexitarians seeking plant-based food and beverages, to date there is no research that allows characterizing and profiling Chilean consumers of plant-based products. Hence, this work seeks to close this gap. To address this problem, we conducted an online survey of 512 people, mainly focused on the Metropolitan Region and Valparaiso. Using Ward s method, we identified 3 welfare, care for the environment and concern for health are prioritized.